Native cysteine residues are dispensable for the structure and function of all five yeast mitotic septins. Issue 11 (19th August 2013) - de, Natalia; McMurray, Michael A.; Lam, Lisa H.; Hsiung, Chris C.‐S.; Bertin, Aurélie; Nogales, Eva; Thorner, Jeremy
ABSTRACT Budding yeast septins assemble into hetero‐octamers and filaments required for cytokinesis. Solvent‐exposed cysteine (Cys) residues provide sites for attaching substituents useful in assessing assembly kinetics and protein interactions. To introduce Cys at defined locations, site‐directed mutagenesis was used, first, to replace the native Cys residues in Cdc3 (C124 C253 C279), Cdc10 (C266), Cdc11 (C43 C137 C138), Cdc12 (C40 C278), and Shs1 (C29 C148) with Ala, Ser, Val, or Phe. When plasmid‐expressed, each Cys‐less septin mutant rescued the cytokinesis defects caused by absence of the corresponding chromosomal gene. When integrated and expressed from its endogenous promoter, the same mutants were fully functional, except Cys‐less Cdc12 mutants (which were viable, but exhibited slow growth and aberrant morphology) and Cdc3(C124V C253V C279V) (which was inviable). No adverse phenotypes were observed when certain pairs of Cys‐less septins were co‐expressed as the sole source of these proteins. Cells grew less well when three Cys‐less septins were co‐expressed, suggesting some reduction in fitness. Nonetheless, cells chromosomally expressing Cys‐less Cdc10, Cdc11, and Cdc12, and expressing Cys‐less Cdc3 from a plasmid, grew well at 30°C. Moreover, recombinant Cys‐less septins—or where one of the Cys‐less septins contained a single Cys introduced at a new site—displayed assembly properties in vitro indistinguishable from wild‐type. Proteins 2013; 81:1964–1979. © 2013 Wiley Periodicals, Inc.